Diseño de una metodología de auditoría de cumplimiento de las obligaciones con las entidades de control que rigen actualmente a las consultoras. Caso: Trazados Cía. LTDA. - Gómez Guallichico, Adriana Mariela (2015)
The degree work I present below, aims to make the design of a methodology for auditing compliance with the obligations with control entities that currently govern the consultants, which is justified by the lack of a comprehensive model that measures the level of compliance of these companies, the same is applied to the consulting Trazados Cía. Ltda.; for which I have conducted research of theoretical sources that support this work as everything related to the Compliance Audit, definitions, processes and phases. Then I made a corporate analysis to Trazados, Which is all about its constitution, its management, its organizational structure, operational and economic environment as well as the procedures necessary for the fulfillment of obligations to control entities. You can see the proposed audit methodology applied to the consultants as a tool to learn, evaluate and recommend using a corrective action report system internal control procedures in compliance with obligations to control entities, and that repeatedly breach causes fines, delays in operations, limitations on certain important services for companies. Finally we can see the case study of the application of this design procedures of compliance with obligations of the Trazados, as being a company that works with the state, participates in tenders and public procurement, may not have outstanding obligations.